Distribution and Dispersal of Phlebotomus papatasi (Diptera: Psychodidae) in a Zoonotic Cutaneous Leishmaniasis Focus, the Northern Negev, Israel - Orshan, Laor (PLoS Negl Trop Dis, 2016)
BACKGROUND: Zoonotic cutaneous leishmaniasis has long been endemic in Israel. In recent years reported incidence of cutaneous leishmaniasis increased and endemic transmission is being observed in a growing number of communities in regions previously considered free of the disease. Here we report the results of an intensive sand fly study carried out in a new endemic focus of Leishmania major. The main objective was to establish a method and to generate a data set to determine the exposure risk, sand fly populations' dynamics and evaluate the efficacy of an attempt to create "cordon sanitaire" devoid of active jird burrows around the residential area. METHODOLOGY/PRINCIPAL FINDINGS: Sand flies were trapped in three fixed reference sites and an additional 52 varying sites. To mark sand flies in the field, sugar solutions containing different food dyes were sprayed on vegetation in five sites. The catch was counted, identified, Leishmania DNA was detected in pooled female samples and the presence of marked specimens was noted. Phlebotomus papatasi, the vector of L. major in the region was the sole Phlebotomus species in the catch. Leishmania major DNA was detected in ~10% of the pooled samples and the highest risk of transmission was in September. Only a few specimens were collected in the residential area while sand fly numbers often exceeded 1,000 per catch in the agricultural fields. The maximal travel distance recorded was 1.91km for females and 1.51km for males. The calculated mean distance traveled (MDT) was 0.75km. CONCLUSIONS: The overall results indicate the presence of dense and mobile sand fly populations in the study area. There seem to be numerous scattered sand fly microsites suitable for development and resting in the agricultural fields. Sand flies apparently moved in all directions, and reached the residential area from the surrounding agricultural fields. The travel distance noted in the current work, supported previous findings that P. papatasi like P. ariasi, can have a relatively long flight range and does not always stay near breeding sites. Following the results, the width of the "cordon sanitaire" in which actions against the reservoir rodents were planned, was extended into the depth of the agricultural fields.